A role of autophagy in PTP4A3-driven cancer progression. - MURRAY, JAMES (My University, 2014)
Autophagy, a "self-eating" cellular process, has dual roles in promoting and suppressing tumor growth, depending on cellular context. PTP4A3/PRL-3, a plasma membrane and endosomal phosphatase, promotes multiple oncogenic processes including cell proliferation, invasion, and cancer metastasis. In this study, we demonstrate that PTP4A3 accumulates in autophagosomes upon inhibition of autophagic degradation. Expression of PTP4A3 enhances PIK3C3-BECN1-dependent autophagosome formation and accelerates LC3-I to LC3-II conversion in an ATG5-dependent manner. PTP4A3 overexpression also enhances the degradation of SQSTM1, a key autophagy substrate. These functions of PTP4A3 are dependent on its catalytic activity and prenylation-dependent membrane association. These results suggest that PTP4A3 functions to promote canonical autophagy flux. Unexpectedly, following autophagy activation, PTP4A3 serves as a novel autophagic substrate, thereby establishing a negative feedback-loop that may be required to fine-tune autophagy activity. Functionally, PTP4A3 utilizes the autophagy pathway to promote cell growth, concomitant with the activation of AKT. Clinically, from the largest ovarian cancer data set (GSE 9899, n = 285) available in GEO, high levels of expression of both PTP4A3 and autophagy genes significantly predict poor prognosis of ovarian cancer patients. These studies reveal a critical role of autophagy in PTP4A3-driven cancer progression, suggesting that autophagy could be a potential Achilles heel to block PTP4A3-mediated tumor progression in stratified patients with high expression of both PTP4A3 and autophagy genes.
PUBLISHED
Keywords: cancer progression; Cancer